Diferensiasi dan Startifikasi Sosial - Ainindya Diva Istiklalia (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2026)
This study aims to explore the concepts of social differentiation and social stratification and their relationship with education as a means of social mobility in Indonesia. Using a qualitative approach based on library research, this study reviews academic literature, scholarly journals, and institutional reports from organizations like the OECD and the World Bank. The findings indicate that education plays a dual role—as an agent of upward social mobility and as an instrument of social reproduction that reinforces inequality when access to education is uneven. Social stratification in Indonesia remains influenced by economic status, Power, and educational attainment. Thus, ensuring equitable education quality is crucial For building a fair and inclusive society. The study recommends educational policies focused on social justice, equitable distribution of educational resources, and the strengthening of equality values at all educational levels.